2019
DOI: 10.1021/acssuschemeng.9b00850
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bis(pyrrolidone)-Based Dicarboxylic Acids in Poly(ester–amide)-Based Thermosets: Synthesis, Characterization, and Potential Route for Their Chemical Recycling

Abstract: In this study, we report on the synthesis and characterization of thermosets based on the renewable N,N′-octamethylene-bis­(pyrrolidone-4-carboxylic acid) (BP-C8) and 1,3-bis­(4,5-dihydro-2-oxazolyl)­benzene (IAox). The BP-C8, having two pyrrolidone rings, is obtained via a bulk aza-Michael addition reaction of 1,8-diaminooctane with 2 equiv of itaconic acid using water as catalyst. Thermosets are prepared by mixing the desired ratio of BP-C8 with IAox, followed by thermal curing at 180 °C. The cross-link dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…It presented internal conversion between linear polymers and cyclic ester amides via ring-closing depolymerization and ring-opening polymerization. Later, the additive reaction between aliphatic dicarboxylic acids and bis­(pyrrolidone), on behalf of the cyclic imino ether class, was also made good use of by several researchers producing another novel option for PEAs synthesis. …”
Section: Synthesis Of Poly(ester Amide)smentioning
confidence: 99%
“…It presented internal conversion between linear polymers and cyclic ester amides via ring-closing depolymerization and ring-opening polymerization. Later, the additive reaction between aliphatic dicarboxylic acids and bis­(pyrrolidone), on behalf of the cyclic imino ether class, was also made good use of by several researchers producing another novel option for PEAs synthesis. …”
Section: Synthesis Of Poly(ester Amide)smentioning
confidence: 99%
“…Lastly, BPDA monomer based on 1,10-dodecanediamine ( c ) was co-polymerized into poly(ester amide)s with sebacic acid, 1,10-dodecanediamine, and 1,4-butanediol, where it was shown that adding BPDA monomer could suppress crystallization (Wang et al, 2016). BPDA monomers based on aliphatic diamines ( c , e.g., is 1,2-ethylene diamine or 1,12-dodecanediamine) can be polymerized with various bis(2-oxazoline)s ( h , e.g., Y is 2,5-furan or 1,3-phenylene) to yield linear or cross-linked amorphous poly(ester amide)s with a T g ranging from 60 to 120°C (Roy et al, 2018, 2019).…”
Section: State Of the Artmentioning
confidence: 99%
“…Hence, the presence of amide moieties confers polyamides with good mechanical and thermal properties. There are many research studies about incorporating amide groups into macromolecular backbones to enhance the properties of materials. For example, Yuan et al fabricated a thermoplastic elastomer which consisted of poly­(tetramethylene glycol) with polyamide 6 (PA6) together . Due to the incorporation of amide bonds into the backbones of polyether glycols, the mechanical and thermal properties of thermoplastic elastomers were improved dramatically.…”
Section: Introductionmentioning
confidence: 99%